Mapping the Pax6 3’ untranslated region microRNA regulatory landscape - Bridget C. Ryan; Kieran Lowe; Laura Hanson; Talveen Gil; Lauren Braun; Perry L. Howard; Robert L. Chow (BMC Genomics, 2018)
Abstract Background PAX6 is a homeodomain transcription factor that acts in a highly dosage-sensitive manner to regulate the development and function of the eyes, nose, central nervous system, gut, and endocrine pancreas. Several individual microRNAs (miRNA) have been implicated in regulating PAX6 in different cellular contexts, but a more general view of how they contribute to the fine-tuning and homeostasis of PAX6 is poorly understood. Results Here, a comprehensive analysis of the Pax6 3′ untranslated region was performed to map potential miRNA recognition elements and served as a backdrop for miRNA expression profiling experiments to identify potential cell/tissue-specific miRNA codes. Pax6 3’UTR pull-down studies identified a cohort of miRNA interactors in pancreatic αTC1–6 cells that, based on the spacing of their recognition sites in the Pax6 3’UTR, revealed 3 clusters where cooperative miRNA regulation may occur. Some of these interacting miRNAs have been implicated in α cell function but have not previously been linked to Pax6 function and may therefore represent novel PAX6 regulators. Conclusions These findings reveal a regulatory landscape upon which miRNAs may participate in the developmental control, fine-tuning and/or homeostasis of PAX6 levels.